Effects of Exosomes Derived From Helicobacter pylori Outer Membrane Vesicle-Infected Hepatocytes on Hepatic Stellate Cell Activation and Liver Fibrosis Induction - Zahmatkesh, Masoumeh Ebadi; Jahanbakhsh, Mariyeh; Hoseini, Negin; Shegefti, Saina; Peymani, Amir; Dabin, Hossein; Samimi, Rasoul; Bolori, Shahin (Frontiers in Cellular and Infection Microbiology, 2022)
Liver fibrosis is a multifactorial disease with microbial and non-microbial causes. In recent years, Helicobacter pylori infection has been thought to play a critical role in some extra-gastrointestinal manifestations especially liver disorders. Outer membrane vesicles (OMVs) are one of the most important discussed H. pylori virulence factors. In the current study, four different clinical strains of H. pylori were collected and their OMVs were purified using ultra-centrifugation. To investigate their effects on liver cell exosomes, co-incubation with hepatocytes was applied. After a while, hepatocyte-derived exosomes were extracted and incubated with hepatic stellate cells (HSCs) to investigate the HSC activation and fibrosis marker induction. The expression of α-SMA, TIMP-1, β-catenin, vimentin, and e-cadherin messenger RNAs (mRNA) was assessed using real-time RT-PCR, and the protein expression of α-SMA, TIMP-1, β-catenin, vimentin, and e-cadherin was evaluated by Western blotting. Our results showed that infected hepatocyte-derived exosomes induced the expression of α-SMA, TIMP-1, β-catenin, and vimentin in HSCs and e-cadherin gene and protein expression was downregulated. In the current study, we found that H. pylori-derived OMVs may aid the exosome alternation and modified exosomes may have a possible role in HSC activation and liver fibrosis progression.